COVID-19 PANDEMIC: ANATOMY STUDY AND ATTITUDE TOWARDS OWN BODY DONATION IN MEDICINE STUDENTS (2020-2021) - Susana N. Biasutto (Asociación Argentina de Anatomía Clínica, 2021)
The COVID-19 pandemic affected all activities. In the university environment, the areas where practical activity is essential were very difficult to compensate for the training deficit. Within the basic subjects of Health Sciences, Anatomy students suffered from the impossibility of accessing cadaveric material, but also many other resources. The objective of this study was to assess the opinion of the students regarding the changes imposed by the pandemic and their attitude towards donating their own bodies. Material and Method: A voluntary survey was carried out to the students who attended in 2020 and 2021, with different levels of restrictions and information regarding donation. The questions referred to demographic data, importance that is assigned to the bodies for the learning of Anatomy, if they were student assistants in that period, if the pandemic affected their training, if they know that the body can be donated and that the Faculty has a program, if they would like to obtain more information, collaborate and / or donate their own body. The results showed great similarity, except that Group 2 had less knowledge of the possibility of donating and the existence of a program, without affecting the will to donate. Also the reasons for not donating were a bit more ambiguous in that group. In addition, some results were compared with similar groups from 2018, showing that the study groups valued cadaveric material less but had a more positive attitude towards donation.